A dopamine antagonist, domperidone enhances the replication of an oncolytic adenovirus in human tumour cells. (22nd June 2022) - Nishimae, Fumitaka; Sakurai, Fuminori; Ono, Ryosuke; Onishi, Rika; Takayama, Kosuke; Mizuguchi, Hiroyuki
Abstract : Oncolytic adenoviruses (OAds) have attracted much attention as novel anticancer agents. Numerous studies have examined the antitumour effects of combinational use of an OAd and anticancer agents; however, few chemical compounds enhancing OAd infection have been reported. In this study, we screened a food and drug administration (FDA)-approved drug library containing 1134 small chemical compounds to identify chemical compounds that enhance OAd replication in human tumour cells. We found that domperidone, a dopamine D2 receptor antagonist, significantly enhanced the replication of an OAd in human tumour cells, including human pancreatic tumour cells, by two–fivefold, resulting in improvement of OAd-mediated tumour cell killing activities. The E1A mRNA levels were significantly increased in domperidone-pre-treated cells following OAd infection, which contributed to the promotion of OAd replication. However, mRNA levels of the dopamine D2 receptor (DRD2), which is known to be a target molecule of domperidone, were undetectable in most of the tumour cells by real-time reverse transcription (RT)-PCR analysis, indicating that domperidone promoted OAd replication by acting on a molecule other than DRD2. This study provides important clues for the improvement of OAd-mediated cancer therapy.